ACTIVE AND DIGITAL LEARNING METHODS IN EDUCATION - Abildinova , G.; Kazhiakparova , Zh.; Abykenova , D.; Assainova, A.; Sembayev, T. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The “Training of university teachers to integrate active teaching methods in digital technologies” program aims to transform Kazakhstan’s higher education teaching methods by incorporating Case-Based Learning (CBL), Problem-Based Learning (PBL), Team-Based Learning (TBL), and digital technology. Designed to align with global standards, the program seeks to enhance teaching effectiveness and integrate modern technologies through diverse sessions, strategic sequencing, and case studies for real-world relevance. It covers active learning and digital technology modules, reinforced by case studies showcasing practical outcomes. The initiative aligns with national educational reform goals, with a detailed implementation and evaluation strategy. Future research will assess its long-term impact and scalability, marking a significant step towards modernizing Kazakhstan’s higher education.